EVALUASI PENERAPAN PROMOSI KESEHATAN DALAM PENCEGAHAN PENANGGULANGAN PENYAKIT DEMAM BERDARAH DENGUE MELALUI GERAKAN 3M PLUS DI KOTA PEKANBARU - Suyanto Suyanto; Zahtamal Zahtamal; Tuti Restuastuti; Fifia Chandra; Handayani Handayani (Program Pascasarjana Universitas Riau, 2009)
Dengue Hemoraggic Fever (DHF) can be controlled with active participation of the communityas Indonesia Government promotes Gerakan 3M. To assess the knowledge attitudes aboutdengue and practice of prevention followed by the residents, an interview based cross sectionalKAP study was undertaken in several DHF endemic subdistricts of Pekanbaru in Mei 08 to Nov08. About 111 individuals were interviewed regarding the different aspects of the DHF. Thepretest result showed that out of total respondents, 44% and 77.5% had good knowledge andattitude about Gerakan 3M though only 4.5% practiced Gerakan 3M. To all of respondents,intervention was made by giving health education, and vector control demonstration. After 1week intervention, out of total respondents the level of knowledge and attitude increasedsignificantly to 76% and 83.3% regarding modes of transmission of disease and its prevention.However, only 1% respondents practiced that. This study concluded that the intervention ofGerakan 3M Information Education Communication is effectively to increase communityknowledge and attitude status, but regularly intervention is still needed by community forprevention and control of Dengue/Dengue haemorrhagic fever in practice level.